Analisa Performansi Keamanan Jaringan VPN PPTP dan L2TP/ IPSEC Untuk FTP Server Di Politeknik Negeri Malang - Muliatama Putra Mahardiyanto (Jurnal Jaringan Telekomunikasi, 2016)
Data exchange communication has developed that leads to centralized communication, and to realize this communication, a type of data communication is needed whose data is stored on a server and can be accessed by clients, such as at the Malang State Polytechnic. As an institution engaged in the world of education, the development of data communication is centralized by utilizing the established intranet network. The use of an intranet network allows for data communication that is vulnerable to eavesdropping. To overcome this, use a VPN network. PPTP VPN and L2TP/IPsec VPN have different performances, especially in the level of security provided. In this study, the performance analysis of the PPTP VPN and L2TP/IPsec VPN networks was carried out which was implemented on an FTP Server on a Raspberry Pi server and a Mikrotik router for the VPN configuration. In this study, we designed PPTP VPN and L2TP/IPsec VPN by configuring the Mikrotik RB9412nD-TC router and configuring FTP Server using the proftpd application on the Raspberry Pi server. For security analysis using hacking method to get VPN Server login data and sniffing method to get FTP Server login data, FTP data. For performance analysis using parameters delay, throughput, and packet loss.